Compressive cervical myelopathy due to massive periodontoid calcium pyrophosphate crystal deposition - F. Bobbio-Pallavicini; O. Epis; L. Cavagna; R. Caporali; C. Montecucco (PAGEPress Publications, 2001)
77 year-old man suffering from psoriatic arthropathy presented with progressive myelopathy due to massive deposits of calcium pyrophosphate dihydrate crystals in peri-odontoid tissue. The magnetic resonance imaging and computer tomographic pictures of the involved site are shown and discussed. The clinical spectrum of crystal deposition disease involving the atlo-axial joint is briefly reviewed.